Erratum: Maurya, S., Datar, M.N. & Choudhary, R.K. (2021) Lectotypification of four names in the genus Capparis (Capparaceae). Phytotaxa 500 (2): 125–132. - Maurya, Satish; Datar, Mandar N.; Choudhary, Ritesh Kumar (Phytotaxa, 2021)
N/A